2000
DOI: 10.1111/j.1601-0825.2000.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Structured review of enamel erosion literature (1980–1998): a critical appraisal of experimental, clinical and review publications

Abstract: OBJECTIVE: To attain an objective account of the methods to measure enamel erosion used in 1980–1998 publications, a structured review of the literature was undertaken. METHODS: Inclusion and exclusion criteria were applied to 731 clinical/experimental research and review reportS. Eighty‐five included papers were subsequently rated according to ‘hierarchy of evidence’ guidelines to assess the strength of the report's design and the relevance of the evidence to replicating enamel erosion in vivo in humanS. Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
4
0
1
Order By: Relevance
“…Some of these studies indicated association of acidic drink consumption with tooth wear on palatal surfaces of primary teeth [10-12, 14-18, 20]. There is also scarce clinical evidence concerning the effect of biological and behavioral risk factors on the development and severity of tooth wear in deciduous dentition [21]. The purposes of the present study were to assess the distribution and severity of tooth wear in a sample of 5-7-year-old children living in the city of Piraeus, Greece and to investigate retrospectively the effect of exposure to several erosive and abrasive risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…Some of these studies indicated association of acidic drink consumption with tooth wear on palatal surfaces of primary teeth [10-12, 14-18, 20]. There is also scarce clinical evidence concerning the effect of biological and behavioral risk factors on the development and severity of tooth wear in deciduous dentition [21]. The purposes of the present study were to assess the distribution and severity of tooth wear in a sample of 5-7-year-old children living in the city of Piraeus, Greece and to investigate retrospectively the effect of exposure to several erosive and abrasive risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…This review illustrates the problems that clinicians and researchers have experienced in quantifying tooth erosion. Assessing the degree of erosion in an individual may be difficult [ 32 ], but is important, as it reflects net exposure to the erosive forces and the opposing forces of protection, for example from saliva. Grading erosion present plays a part in the assessment of the problem, the need for treatment and, potentially, may indicate means for prevention of further tooth wear.…”
Section: Introductionmentioning
confidence: 99%
“…Erosion of tooth surfaces occurs when the latter are frequently exposed to acid 1) . A worrying trend emerges in that the prevalence of dental erosion is on the increase.…”
Section: Introductionmentioning
confidence: 99%